(untitled) (Experimental biology, 2024)
In recent years, due to the increasing anthropogenic load on the environment, research has intensified to identify local plants that are accumulators of heavy metals. The article examines the issue of accumulation of heavy metals, in particular Zn, Cd, Pb, Cu in sunflower plants and lawn grasses on the territory of the “Ulbi” metallurgical complex, located in the city of Ust-Kamenogorsk. Currently, the search for plants that store heavy metals is actively underway. Based on a review of literature data, among species with the ability to phytoremediate, sunflower plants (Heliantus annuus L.) and a grass mixture of different phytoremediant species of the cereal family (Agropyron repens (L.) P. Beauv. (wheatgrass), Bromus inermis Leyss. (brome), Agrostis alba L. (bentgrass) and Dactylis glomerata L. (urchin) were used as research objects. The relationship between the degree of soil contamination with heavy metals and the intensity of their entry into plants is shown. Thus, the content of zinc in the soil can be reduced by 22.5%, cadmium by 31%, lead by 40.7%, copper by 29.4%. It has been established that the intensity of absorption of heavy metals is higher in corn plants compared to plants included in the grass mixture. The experimental results may be of interest for the development of technology for phytoremediation of soils contaminated with heavy metals.